Mondo complexes regulate TFEB via TOR inhibition to promote longevity in response to gonadal signals - Nakamura, Shuhei; Karalay, Özlem; Jäger, Philipp S.; Horikawa, Makoto; Klein, Corinna; Nakamura, Kayo; Latza, Christian; Templer, Sven E.; Dieterich, Christoph; Antebi, Adam (Nature Communications, 2016)
Removal of the C. elegans germline substantially increases organismal lifespan. Here, Nakamura et al. show that the transcription factors MML-1 and MXL-2 coordinate this process in that they reduce TOR signalling and increase autophagy by regulating activity of HLH-30.